ANALYSIS OF THROUGH FALL AS EFFECTIVE RAIN INFORMATION IN VEGETATED LANDS - Enni Dwi Wahjunie; Wahyu Purwakusuma; Eko Taufik Wirawan; Sri Malahayati Yusuf; Yayat Hidayat (Sean Institute, 2023)
Rainfall is the water main source on the world. Rainwater that can be used for life is water that reaches the soil surface (effective rain), and then be stored in the soil or as surface runoff that causes flooding. The total of rainwater that reaches the soil surface on vegetated lands is highly dependent on the total of interception (water retained and absorbed by vegetation to then evaporate to atmosphere). The remaining rainwater that is not retained by vegetation will flow through the stem (stem flow) and through fall from the plant canopy to the soil surface. The total of rain water intercepted depends on the nature of the rain and the vegetation. Therefore, this study wanted to examine the total of through fall related to the type of vegetation and the rain characteristics. The research was conducted at Dusun Besar, Kayong Utara Regency, West Kalimantan during the 2021 rainy season, on a slope transect from flat land to hills. The transect was divided into several slope classes, then on each slope class were observed of the vegetation type, rainfall, through fall, and intercept. Observations showed that the through fall in each land use was, teak on slope I (J;I) was 74.81%; Coconut on slope I (K;I) was 74.41%; Durian on slope II (D,II) was 50.64%; Durian on slope IV (D;IV) was 59.58% and forest on slope IV (H;IV) was 54.58%. The greater through fall is in line with the greater and more rain frequent, and the smaller of plant area canopy.